2021
DOI: 10.1111/bjd.19810
|View full text |Cite
|
Sign up to set email alerts
|

A glycopyrronium bromide 1% cream for topical treatment of primary axillary hyperhidrosis: efficacy and safety results from a phase IIIa randomized controlled trial*

Abstract: Summary Background Effective topical treatment options for patients with primary axillary hyperhidrosis (PAHH) are limited. A phase I trial showed promising results regarding the efficacy and safety of a topical cream containing glycopyrronium bromide (GPB). Objectives To assess the efficacy, safety and tolerability of a 4‐week topical treatment of GPB 1% cream in patients with PAHH vs. placebo. Methods In total, 171 patients (84 receiving placebo; 87 receiving GPB 1%) with PAHH were included in the 4‐week, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Topical Sofpironium bromide(ECCLOCK®, 5%) gel reduces sweat secretion by inhibiting local sweat gland M3 muscarinic receptor [37] , approved in Japan in September 2020. In addition, topical preparation of GPB has aroused interest as a treatment option for PHH [38] , and 1% GPB cream has completed the phase IIIa study [39] . A dermal preparation of Umeclidinium (UMEC) ammonium bromide is also under way [40] .…”
Section: Introductionmentioning
confidence: 99%
“…Topical Sofpironium bromide(ECCLOCK®, 5%) gel reduces sweat secretion by inhibiting local sweat gland M3 muscarinic receptor [37] , approved in Japan in September 2020. In addition, topical preparation of GPB has aroused interest as a treatment option for PHH [38] , and 1% GPB cream has completed the phase IIIa study [39] . A dermal preparation of Umeclidinium (UMEC) ammonium bromide is also under way [40] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Pariser et al reported the pharmacokinetic (PK) profile of GP tosylate wipes applied by patients with hyperhidrosis for 4 weeks with a 2-week off-drug follow-up. 4 In view of the likely systemic absorption of topical anticholinergic agents, the possible risks of their long-term use and the potential interindividual variability, especially in elderly patients, we believe that data on the PK profile of the GPB 1% cream formulation for a time period beyond 2 weeks are of great importance in real-world practice and need to be considered and critically evaluated in an appropriately extended clinical trial programme. DEAR EDITOR, Gregoriou et al have asked for systemic pharmacokinetic (PK) data beyond 2 weeks after the topical application of glycopyrronium (GP) bromide (GPB)-containing cream for treatment of primary axillary hyperhidrosis, 1 compared to another recently approved GP tosylate (GPT)-containing topical product.…”
mentioning
confidence: 99%
“…Dear Editor , Abels et al . have reported the results of a phase IIIa randomized placebo‐controlled study assessing the efficacy and safety of a formulation of glycopyrronium (GP) bromide (GPB) 1% cream applied for 4 weeks as a topical treatment for primary axillary hyperhidrosis 1 . In the preceding phase Ib trial, three concentrations of GPB cream were applied topically for 2 weeks: 0·5%, 1% and 2%.…”
mentioning
confidence: 99%
“…The PK data (C max ) of GP are predictive of anticholinergic adverse events (AEs) following topical application regarding frequency and severity. 2 As the frequency of systemic, anticholinergic AEs was lower after treatment with GPB cream than with GPT-containing wipes, 3,4 plasma concentrations after topical application of GPB cream are unlikely to exceed those of GPT-containing wipes.…”
mentioning
confidence: 99%
“…This is not surprising, as 1% cream contains only 0Á8% GP vs. 2Á4% GP in wipes. Local tolerability was clearly worse after the application of the alcoholic wipes, 3,4 indicating impairment of the epidermal barrier and contributing to an increased permeation of GPT.…”
mentioning
confidence: 99%